Itinerário terapeutico de usuários na atenção primária à saúde em triplice fronteira - Lima, Lisete Teixeira Palma de (2017)
The search for health care comes from the individual need to find healing or relief for pain and discomfort, and regardless of the flows, protocols or established norms new paths are drawn, people are involved and the results happen with or without effectiveness or equity. These paths are called therapeutic itineraries. Thus, this study aimed to know the therapeutic itinerary and access of Brazilian users in the public health system, residing in Paraguay or Argentina, in the search for health care in primary care, in the municipality of Foz do Iguaçu, a member of the triple border - Brazil, Paraguay and Argentina. It was developed through qualitative research, using the reference of historical materialism. Data collection was done through semi-structured interviews, with Brazilian residents in Argentina and Paraguay, users of the primary care service in one of the health units in the city of Foz do Iguaçu, Brazil, and in Puerto Iguazu, in Argentine. The data were grouped into units of meaning and their analysis was thematic, with different topics emerging for discussion: In thematic unit one, the therapeutic itinerary is discussed: a look at the triple frontier, through the subthemes: the public and the private in the Health care for brasiguaios; The decision to seek the Unified Health System in Brazil; Access to health services and primary health care as the (des) coordinator of the care network. In Unit Two, Resolving Health Care in Border Region, the findings are discussed through two thematic subunits: reasons for the search for health care in Foz do Iguaçu, Brazil; And, resoluteness found by brasiguaios in the care received in primary care in Brazil. The third unit presents the access and accessibility of Brazilian residents in neighboring countries, in the primary care of Foz do Iguaçu. The results pointed to a primary care that needs to use new tools to increase access and resolution in its work process, coordinating the local health system and, as a consequence, a better management of care. The therapeutic itinerary covered included the three subsystems: family, professional and popular, according to the literature. Difficulties with equity and health information were perceived, since not all users take advantage of health services offers, such as non-resident users. And as for health coverage, examples of using the public - private mix as responses to health imbalances show us that we are far from this goal. However, we found users residing in neighboring countries, satisfied with the service received in Brazil.